Marine Pollution Recent Developments - Mancuso, Monique; Abbas, Mohamed H.H; Bottari, Teresa; Abdelhafez, Ahmed A. (Environmental Sciences, 2023)
This book discusses marine pollution. It includes 10 chapters that attempt to answer the questions of how to reduce marine pollution and what really can be done to improve the quality of the sea. Topics addressed include microplastics, the dispersion of oil in the sea, contamination by potentially toxic elements (PTEs), and much more.